Formulating Customer Discovery of Fervor Nutrition in South Jakarta - arif, Victor; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2017)
Abstract. Fervor Nutrition is a start-up company that was established in 2016 and was found by Victor Arif (as Chief Executive Officer or CEO) and Wanda Pradipta (as Operational Manager). Fervor Nutrition moves in nutrition industries. Fervor Nutrition is focus on human body nutrition and to give people the best experience in use of the Fervor Nutrition products as theirs diet. Fervor Nutrition want to give customers, the solutions of the needs and problems of the customer nutrition, and give customer the best nutrition for people who want improve their body and keep fit. Fervor Nutrition will focus in grab fast protein drink with product name ISOPRO. In this research, Fervor Nutrition as a start-up is using Customer Discovery to search problem-solution fit, i.e. a product market fit, that makes the start-up’s value proposition match the customer segment the start-up envisions reaching. To facilitate the Customer Discovery process and get a shared and clear understanding of the business model throughout the company, Fervor Nutrition begins the first phase by stating the Business Model Canvas hypothesis. The Business Model Canvas represents the company in nine boxes that depict the details of a company’s products, customers, distribution channels, demand creation, revenue model, partners, resources, activities and cost structure. On the second phase, Fervor Nutrition will be testing the problem by preparing customer contact and engagement, the goal is to learn about the problem and not to talk about the product or its features, and The Problem Presentation that is designed to elicit information from customers. After enough interviews Fervor Nutrition should be able to determine what the customer problem is and update the hypothesis accordingly. The third phase is testing the solution which consists of five key steps; create the product / solution presentation with the revised hypotheses that can be presented to customers, test the product solution with the customer by measuring enthusiasm most of all, update the business model again to reflect the latest round of Customer Discovery “solution” findings. In the last phase Fervor Nutrition should have identified a serious problem to have solved by solution and identified a large enough market to create a scalable business model. If these criteria are met and the business model is solid, Fervor Nutrition should continue to the next step, to Customer Validation. If the criteria are not met, go back to Customer Discovery or pivot. In order to solving these issue, the methodological approach would be integrating quantitative and qualitative data. For qualitative data, would be get through interviews, meanwhile the quantitative data would be get through questionnaire. Which in result, according to Business Model Hypothesis, Problem Presentation, and Business Model Canvas Improved.Keywords: Formulating Strategy, Customer Development, Customer Discovery, Business Model, Start-up Company, Nutrition Products, Protein Drink, Protein Shake, Beverage